Professional football training and recovery: A longitudinal study on the effects of weekly conditioning session and workload variables - Curzi, D.; Amatori, S.; Silvestri, F.; Marcelli, L.; Campanella, M.; Perroni, F.; Gallotta, M. C.; Favoriti, A.; Baldari, C.; Guidetti, L. (PLOS ONE, 2024)
The main purpose of this longitudinal study was to investigate football players` recovery status, through hormonal response, in relation to accumulated workload at two comparable time points of the first (T1) and second half (T2) of the competitive season. Moreover, this study investigated athletes` hormonal response to a typical weekly conditioning session (5 days before match: MD-5), at T1 and T2, to detect changes in players` recovery capability over time. Salivary cortisol (sC) and testosterone (sT) of 24 professional players (27.8 ± 4.1 years of age) were collected before, after, and 24 hours following MD-5 in two comparable microcycles of T1 and T2. GPS training data (total and high-intensity distance) of the 7 and 28 days before sampling were used to obtain athletes` acute and chronic workloads. Results showed a pre-training significant decrease of sT and an increase of sC (p<0.05) in T2, compared to T1. Moreover, athletes showed high sC and low sT levels before, after and 24 hours following MD-5 in T2. Workload analysis revealed significant correlations of chronic load with sC (r = 0.45, p = 0.056) and T/C ratio (r = -0.59; p = 0.007). These results suggested that, in professional football, chronic workload has a greater impact on players` recovery time than acute workload over the sport season. Moreover, athletes` hormonal response to the weekly conditioning session at T2 revealed an altered anabolic/catabolic balance, highlighting the key role of continuous internal and external workload monitoring during the season.